Millennial utopians and prepper subcultures: Contemporary utopianism on the left and right. (February 2021) - McKenzie, Jordan
Highlights: This paper considers two examples of contemporary future thinking: Millennial utopians and preppers/survivalists. The analysis is based on texts in the Millennial utopian genre, and interview and ethnographic research on survivalists. The findings show that attempts at future oriented action are pushed to the fringes of the left/right political spectrum. The article highlights optimism, pessimism, hope and nostalgia in the politics of future thinking. Abstract: There is a common feeling that the apocalypse is not as abstract or far away as it once was (Riederer, 2018 ; Wallerstein, Collins, Mann, Derluguian, & Calhoun, 2013 ). This paper will consider two examples of contemporary future thinking: Millennial utopians and preppers/survivalists. While these groups can be seen as symptomatic of left and right political divides, the investigation of these groups is not intended to be representative of the left or the right. Instead, they demonstrate how the theory and praxis of future oriented ideas are found at the fringes rather than at the centre of contemporary socio-political debates. While these groups differ in fundamental ways, they both offer a demonstration of what 'taking the future seriously' might look like in the contemporary West. This paper will unpack the utopian and dystopian elements of both movements and decipher their appeal in an age of increased anxiety about the future.